The safety of mepolizumab for the treatment of asthma. Issue 3 (4th March 2017) - Leung, E; Al Efraij, K; FitzGerald, JM
ABSTRACT: Introduction : Asthma is an airway disease characterized by airway inflammation. It is associated with significant morbidity, mortality, and costs to the healthcare system and society. Interleukin-5 (IL-5) was identified for its role in eosinophil development, maturation, and survival in tissues, which has been related to disease severity and airway eosinophilia. Areas covered : In this review, we will present the pharmacokinetics and dynamics of mepolizumab in addition to efficacy and safety data. Expert Opinion : Mepolizumab is novel, new, first-in-class therapy targeting IL-5. It has been found to be particularly effective in the management of patients with asthma whose peripheral blood eosinophil count is at a well-defined cut point within the normative range. This easily available biomarker, along with a history of asthma exacerbations, has translated into a clinically significant reduction in asthma exacerbations and the dose of oral corticosteroids in patients who previously have been prednisone-dependent. The pivotal studies indicate that mepolizumab was well tolerated, with the most frequently reported adverse events being headache, nasopharyngitis, worsening of asthma, and local injection reactions. These study investigators did not report any deaths or anaphylaxis related to mepolizumab.